2022
DOI: 10.3389/fpsyt.2022.854698
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Threat Avoidability of COVID-19 on Coping Strategies and Psychic Anxiety Among Chinese College Students in the Early Stage of COVID-19 Pandemic

Abstract: BackgroundThe novel coronavirus disease 2019 (COVID-19) outbreak has seriously threatened the mental health of college students. This study intended to invest whether perceived threat avoidability of COVID-19 relates to psychic anxiety among college students during the early stage of the COVID-19 pandemic, as well as the mediating roles of COVID-19-specific wishful thinking and COVID-19-specific protective behaviors in this relationship.MethodsA cross-sectional study was conducted in China, using a random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In this sample, wishful thinking proved to increase dissociative experiences overall, and all its subscales through the mediation of perceived stress, and had a direct increasing effect on absorption and depersonalization. Wu et al [75] found the same adverse effect when examining effects of COVID-specific wishful thinking of Chinese university students and found that wishful thinking strategy increased anxiety and also prevented students from adaptive protective behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…In this sample, wishful thinking proved to increase dissociative experiences overall, and all its subscales through the mediation of perceived stress, and had a direct increasing effect on absorption and depersonalization. Wu et al [75] found the same adverse effect when examining effects of COVID-specific wishful thinking of Chinese university students and found that wishful thinking strategy increased anxiety and also prevented students from adaptive protective behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…In this sample, wishful thinking proved to increase dissociative experiences overall, and in all its subscales through the mediation of perceived stress, and had a direct increasing effect on absorption and depersonalization. Wu et al [ 81 ] found the same adverse effect when examining the effects of COVID-specific wishful thinking of Chinese university students and found that the wishful thinking strategy increased anxiety and also prevented students from adaptive protective behaviors.…”
Section: Discussionmentioning
confidence: 88%
“…Using wishful thinking as a coping strategy means that participants fantasize a better future while avoiding or suppressing thoughts about the pandemic reality that is simply too overwhelming to deal with. However, despite the initial intent of reducing stress, wishful thinking has found to increase people’s level of anxiety during the COVID-19 pandemic instead (Wu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%